2004
DOI: 10.5172/conu.16.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Community health nursing in Australia: A critical literature review and implications for professional development

Abstract: Community health nursing in Australia has a low professional profile when compared to other nursing specialties. An emerging issue, gleaned from the literature review is the tension and debate between specialist and generalist services. It is apparent from this review that CHN have to more actively participate in research and peer reviewed debate in order to have their voice heard and promote their unique and valuable contribution to the nursing profession and the health care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 18 publications
0
26
0
1
Order By: Relevance
“…They, however, face a number of barriers, in particular a lack of time and funding [9-12]. Generalist community nurses (GCNs) in Australia are also in a good position to offer individual lifestyle intervention, because they (a) often see patients with existing chronic conditions that might benefit from lifestyle change; (b) often have ongoing contact with patients over an extended period of time; (c) mostly see clients in their own homes, and can observe the living environment and involve the wider family/carers in the intervention; and (d) may reach disadvantaged individuals with limited contact with general practice [13,14]. Our previous research has shown that GCNs see lifestyle intervention as appropriate to their role and philosophy of providing holistic care, although some thought the age of their client group limited the scope for lifestyle change [15].…”
Section: Introductionmentioning
confidence: 99%
“…They, however, face a number of barriers, in particular a lack of time and funding [9-12]. Generalist community nurses (GCNs) in Australia are also in a good position to offer individual lifestyle intervention, because they (a) often see patients with existing chronic conditions that might benefit from lifestyle change; (b) often have ongoing contact with patients over an extended period of time; (c) mostly see clients in their own homes, and can observe the living environment and involve the wider family/carers in the intervention; and (d) may reach disadvantaged individuals with limited contact with general practice [13,14]. Our previous research has shown that GCNs see lifestyle intervention as appropriate to their role and philosophy of providing holistic care, although some thought the age of their client group limited the scope for lifestyle change [15].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, although the findings of this study represent the views of Canadian CHNs, those in other countries, including the United Kingdom and Australia, face similar trends and issues in community health nursing practice (Brookes, Davidson, Daly, & Hancock, 2004;Cook, 2009;Drennan, Andrews, Sidhu, & Peacock, 2006). Collaborative action-oriented discussions with international colleagues can provide promising opportunities to advance community health nursing practice globally.…”
Section: Discussionmentioning
confidence: 79%
“…20 As a consequence of these prolonged illness trajectories communitybased services are frequently required to provide care for extended periods of time. 21,22 Absence of palliative care beds As there are no designated beds on the mid-north coast, palliative care patients requiring inpatient care are admitted to one of five local hospitals. A recent planning framework has estimated that 6.7 designated palliative care beds are required for this population.…”
Section: Increased Demand For Servicesmentioning
confidence: 99%